(3GdfhQ GddGFM hGdOQ GdUGOM aj GUWaGA ehdGfG Gdedc GdUGdMs - (3EHQGgje Hf YHO GdQMef Hf YHO Gddg, TeS GdOjf GdbjSQGfj,J (B753 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CUdM TCf GdCeI s
(3Gdedc GdUGdM gh ESeGYjd Hf eMeO Hf bdGhhf GdfSNI ahJhZQGa Yf fSNI HGQjS GdJi HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B46s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B24 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B281 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs